2017
DOI: 10.1177/2325967117726521
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hip Pain and Function in Femoroacetabular Impingement: A Prospective Cohort Analysis

Abstract: Background:Validated patient-reported outcome measures (PROMs) of hip pain and function at the time of arthroscopy could be predictors of the final outcome. Little is known about how patient factors or pathologic intra-articular findings relate to hip pain or function at the time of surgery for those presenting with femoroacetabular impingement (FAI).Purpose:To evaluate all patient and operative factors that contribute to hip pain and dysfunction in patients with FAI.Study Design:Cross-sectional study; Level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 27 publications
4
65
4
Order By: Relevance
“…), further supporting the lack of correlation between sFLCs and markers of disease severity. An important consideration when using PROMs is the importance of patient characteristics, such as mental health, activity level, smoking status, and sex in determining outcomes, rather than just underlying pathophysiology . Interestingly, although sFLCs did not correlate with FAI symptoms in this study, CRP has previously been shown to correlate with symptoms in osteoarthritis .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…), further supporting the lack of correlation between sFLCs and markers of disease severity. An important consideration when using PROMs is the importance of patient characteristics, such as mental health, activity level, smoking status, and sex in determining outcomes, rather than just underlying pathophysiology . Interestingly, although sFLCs did not correlate with FAI symptoms in this study, CRP has previously been shown to correlate with symptoms in osteoarthritis .…”
Section: Discussioncontrasting
confidence: 62%
“…An important consideration when using PROMs is the importance of patient characteristics, such as mental health, activity level, smoking status, and sex in determining outcomes, rather than just underlying pathophysiology. 38 Interestingly, although sFLCs did not correlate with FAI symptoms in this study, CRP has previously been shown to correlate with symptoms in osteoarthritis. 10 This could be explained by systemic inflammation playing less of a role in FAI than osteoarthritis, or perhaps due to the different inflammatory pathways stimulating CRP and sFLC production.…”
Section: Prognostic Markerscontrasting
confidence: 69%
“…35 Psychological distress and mental health disease are increasingly recognized as significant influences on pain and function associated with orthopedic conditions. 21,[36][37][38][39][40] In a previous study, preoperative predictors of increased baseline (preoperative) pain and decreased baseline function included mental health, activity level, sex, and smoking. 21 Psychological distress was reported to negatively affect both baseline hip pain and function scores at the time of hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…21,[36][37][38][39][40] In a previous study, preoperative predictors of increased baseline (preoperative) pain and decreased baseline function included mental health, activity level, sex, and smoking. 21 Psychological distress was reported to negatively affect both baseline hip pain and function scores at the time of hip arthroscopy. 41 Poor mental health scores were subsequently identified as independent risk factors for increased baseline pain prior to hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation